New Syllabus Primary Mathematics - Dr Foong Pui Yee (Oxford university press, 2019)
New Syllabus Primary Mathematics: A Comprehensive Mathematics Series for Grade 1 is designed as part of a mathematics series aimed at young learners, specifically for Grade 1 students. The book provides a structured approach to introducing fundamental mathematical concepts, ensuring that students build a solid foundation in mathematics from an early age.The primary goal of this book is to support young learners in acquiring essential mathematical skills and fostering a positive attitude toward learning mathematics. It is intended to complement classroom instruction and provide additional practice and reinforcement.
Keywords: Textbook Maths -- Textbook